2017
DOI: 10.21873/anticanres.11424
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Study of Vasculogenic Mimicry and Angiogenesis in Melanocytic Tumors of the Eye and the Periocular Area

Abstract: The existence of vasculogenic mimicry in benign nevi might have prognostic implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“… 17 , 27 In benign nevi, IHC analysis of VM was shown in a minority of cases as compared to that of melanomas and was associated with unfavorable survival. 60 In a patient diagnosed with multiple probable cerebral cavernous malformations, a slightly enlarged hyperintense region on the right frontal lobe persisted after therapy. Postoperative histological diagnosis demonstrated an anaplastic oligodendroglioma and cerebral cavernous malformations with VM.…”
Section: Introductionmentioning
confidence: 99%
“… 17 , 27 In benign nevi, IHC analysis of VM was shown in a minority of cases as compared to that of melanomas and was associated with unfavorable survival. 60 In a patient diagnosed with multiple probable cerebral cavernous malformations, a slightly enlarged hyperintense region on the right frontal lobe persisted after therapy. Postoperative histological diagnosis demonstrated an anaplastic oligodendroglioma and cerebral cavernous malformations with VM.…”
Section: Introductionmentioning
confidence: 99%
“…However, the expression of EPH receptor A2 (EphA2), a potential indicator of VM formation, was not remarkably regulated after overexpressing L1 in glioma cells, suggesting that the EphA2 signal might not be associated with L1‐mediated VM formation in glioma. Similarly, immunofluorescence staining further confirmed that the expression of CD31 and CD34, which are the key biomarkers in the VM formation process [48,49], was significantly increased in L1‐overexpressing T98 and GBM1 cells (Fig. 3C).…”
Section: Resultsmentioning
confidence: 59%
“…It is likely that melanocytic malignant tumors such as melanoma arising from the ocular regions revealed more vascular-rich nature than non-malignant melanocytic tumors (9). In this study, in aspirating the iris tumor tissue for the diagnosis, intraoperative and postoperative bleeding was not apparent in the anterior chamber, suggesting that metastatic iris tumors might be characterized by hypovascular non-melanocytic tumors.…”
Section: Discussionmentioning
confidence: 65%